2005
DOI: 10.2214/ajr.184.6.01841774
|View full text |Cite
|
Sign up to set email alerts
|

MRI Measurements of Breast Tumor Volume Predict Response to Neoadjuvant Chemotherapy and Recurrence-Free Survival

Abstract: MRI tumor volume was more predictive of RFS than tumor diameter, suggesting that volumetric changes measured using MRI may provide a more sensitive assessment of treatment efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
176
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(190 citation statements)
references
References 32 publications
6
176
0
4
Order By: Relevance
“…Although this reduction may appear dramatic, it is fully consistent with the results reported by Nonaka et al (2012), who observed a 97% volume reduction of human hepatocellular carcinoma after 3 weeks of subcutaneous injection with GcMAF. It is also consistent with the results reported for neoadjuvant chemotherapy (Partridge et al, 2005).…”
Section: Resultssupporting
confidence: 93%
“…Although this reduction may appear dramatic, it is fully consistent with the results reported by Nonaka et al (2012), who observed a 97% volume reduction of human hepatocellular carcinoma after 3 weeks of subcutaneous injection with GcMAF. It is also consistent with the results reported for neoadjuvant chemotherapy (Partridge et al, 2005).…”
Section: Resultssupporting
confidence: 93%
“…Tumour volumes were measured, rather than more typical linear measurements, as this was considered to be the most rigorous and accurate, although most time-consuming, way of quantifying lesion size. Tumour volume has been shown to correlate more closely than tumour diameter with disease-free survival in breast cancer patients and it may also provide a more sensitive characterisation of tumour response than one-dimensional measurements (Partridge et al, 2005).…”
Section: Mr Imaging and Spectroscopymentioning
confidence: 99%
“…However, they also found that patients achieving both clinical and ultrasound complete responses, and not undergoing surgery, had a low (8%) rate of locoregional recurrence at 5 years. Additionally, MRI has also proven to be useful in the assessment of the tumour response to chemotherapy (Thibault et al, 2004;Warren et al, 2004;Partridge et al, 2005;Segara et al, 2007). This good value of MRI in the evaluation of tumour response should also apply to ILC as, even though ILC is still a challenge for MRI (Kinkel and Hylton, 2001), the addition of MRI to mammography still increases the sensitivity in the detection of ILC (Gilles et al, 1994;Sittek et al, 1998) and, most importantly in the case of the response evaluation, the volumetric assessment is improved (Boetes et al, 2004;Fabre Demard et al, 2005;Caramella et al, 2007;Mann et al, 2008).…”
Section: Discussionmentioning
confidence: 99%